Force-Field Derivation and Atomistic Simulation of HMX/Graphite Interface and Polycrystal Systems - 龙瑶 刘永刚 聂福德 陈军 (Communications in theoretical physics, 2012)
Interface is the key issue to understand the performance of composite materials. In this work, we study the interface between octahydro-1,3,5,7-tetranitro-1,3,5,7-tetrazocine （HMX） and graphite, try to find out its contribution to mixture explosives. The work starts from the force-field derivation. We get ab initio based pair potentials across the interface, and then use them to study the interface structural and mechanical properties. A series of large scale molecular dynamics simulations are performed. The structure evolution, energy variation and elastic/plastic transformation of interface and polycrystal systems are calculated. The desensitizing mechanism of graphite to HMX is discussed.